A preparação de atores na montagem de ‘Quatro Paredes’. Goiânia, Brasil (2003). - Peixoto , Bruno Quirino (2015)
This dissertation is due to is a due to thoughts about the process of the coaching of actors from the play Quatro Paredes, by Cia. Mínima in Goiânia, Goiás, Brasil, 2003. This theatrical production was constituted inspired by principles of acting coaching presented by Italian theater director Eugênio Barba (1936) in Brazil and is part of the reception of techniques developed by the director in our country. These work pursuits the systematization and thinking of the methodologies and exercises used in the preparation of actors of this theatrical production. Such analysis uses four conceptual filters for the comprehension of this process and present on the building of this play: ritual, flow, play and improvisation. The methodology used in this is investigated through exercises and procedures that were grounded on these conceptual filters. Through work diary, photos and memories the elements of four actors’ experiences are registered and analyzed during the preparation of the referred play: Ana Paula Carvalho, Bruno Peixoto, Mayarah Pinheiro e Pedro Vilela.